PENERAPAN METODE QUANTUM LEARNING DENGAN LEARNING STYLE VAK (VISUAL, AUDITORIAL, DAN KINESTHETIK) UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS X-3 SMA NEGERI OLAHRAGA PROVINSI RIAU - Susi Andrianty (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2015)
Application of Quantum Learning Method with VAK Learning Style (visual, auditory and kinesthetic) shown to increase the average value of presentation of the group. In the first action to obtain an average value of 0, this is caused by the presentation of the first actions was not performed because the lesson has been exhausted. In the second action to obtain an average value of 77.5. In the third act of obtaining an average value of 80.33. Implementation of action research by applying the method of Quantum Learning with Vak Learning Style (visual, auditory and kinesthetic) can significantly improve the results of class X-3 student of SMA Negeri Olahraga Pekanbaru in sub Pedosphere subject matter. This is evident from the average value of student learning outcomes are assessed on the test, teamwork and presentation continues to increase in every action. The average value before the action is equal to 68.61. In the first act of the average value of student learning outcomes to obtain a value of 26.26, then the second action has risen to obtain a value of 85.21 and in the third act of increased back to the acquisition value of 89.26Keywords: quantum learning, learning outcomes